Advances in the study of TIM3 in myelodysplastic syndrome - Guo, Xinyu; Yu, Shunjie; Tao, Jinglian; Wang, Yingshuai; Shao, Zonghong; Fu, Rong; Li, Lijuan (Frontiers in Immunology, 2025)
Myelodysplastic syndromes (MDS) are heterogeneous myeloid clonal disorders derived from hematopoietic stem cells. The incidence of MDS (1.51/100,000 in China, 4-5/100,000 in Europe and America) is higher than any subtype of leukemia. In recent years, the imbalance of immune regulation and tumor microenvironmental disorders have received increasing attention in the pathogenesis of MDS. T-cell immunoglobulin and mucin-domain containing protein 3 (TIM-3) is an important inhibitory immune checkpoint molecule, widely expressed in T cells, NK cells, and dendritic cells, monocytes/macrophages and other immune cells. Numerous studies have confirmed that TIM-3 is aberrantly expressed in a variety of solid and hematologic tumors and plays an important role in regulating tumor escape and immune depletion. In this paper, we focus on reviewing the relevant studies of TIM-3 in MDS and summarize the findings of our team in this field. We also discuss the potential application of TIM-3 in the diagnosis and treatment of MDS in conjunction with the latest clinical trials. Blocking TIM-3 has both ‘tumor cell-targeted inhibition’ and ‘immune function remodeling’ dual roles in MDS disease progression, which provides new therapeutic strategies and hope for MDS patients.